Efficient Building Blocks for Solid‐Phase Peptide Synthesis of Spin Labeled Peptides for Electron Paramagnetic Resonance and Dynamic Nuclear Polarization Applications. Issue 11 (13th May 2019) - Brodrecht, Martin; Herr, Kevin; Bothe, Sarah; de Oliveira, Marcos; Gutmann, Torsten; Buntkowsky, Gerd
Abstract: Specific spin labeling allows the site‐selective investigation of biomolecules by EPR and DNP enhanced NMR spectroscopy. A novel spin labeling strategy for commercially available Fmoc‐amino acids is developed. In this approach, the PROXYL spin label is covalently attached to the hydroxyl side chain of three amino acids hydroxyproline (Hyp), serine (Ser) and tyrosine (Tyr) by a simple three‐step synthesis route. The obtained PROXYL containing building‐blocks are N‐terminally protected by the Fmoc‐protection group, which makes them applicable for the use in solid‐phase peptide synthesis (SPPS). This approach allows the insertion of the spin label at any desired position during SPPS, which makes it more versatile than the widely used post synthetic spin labeling strategies. For the final building‐blocks, the radical activity is proven by EPR. DNP enhanced solid‐state NMR experiments employing these building‐blocks in a TCE solution show enhancement factors of up to 26 for 1 H and 13 C ( 1 H→ 13 C cross‐polarization). To proof the viability of the presented building‐blocks for insertion of the spin label during SPPS the penta‐peptide Acetyl‐Gly‐Ser(PROXYL)‐Gly‐Gly‐Gly was synthesized employing the spin labeled Ser building‐block. This peptide could successfully be isolated and the spin label activity proved by EPR and DNP NMR measurements, showing enhancement factors of 12.1±0.1 for 1 H and 13.9±0.5 for 13 C (direct polarization). Abstract : A versatile strategy for the spin labeling of peptides by non‐natural amino acids with a nitroxide radical in their side chain is presented. This strategy is fully compatible with solid‐phase peptide synthesis. The success of the labeling and the activity of the radical is demonstrated by electron paramagnetic resonance and dynamic‐nuclear‐polarization‐enhanced solid‐state NMR measurements on a small model peptide.